1997
DOI: 10.1046/j.1570-7458.1997.00190.x
|View full text |Cite
|
Sign up to set email alerts
|

Mortality of eggs, larvae and pupae and larval dispersal of the cabbage moth, Mamestra brassicae, in white cabbage in south‐eastern Norway

Abstract: The mortality of eggs, larvae and pupae and larval dispersal of the cabbage moth, Mamestra brassicae (L.) (Lepidoptera: Noctuidae) was investigated in a series of small‐scale field experiments in white cabbage, Brassicae oleracea var. capitata (L.), and in the laboratory during 1990–1992 in south–eastern Norway. The highest mortality was found in young larvae and in hibernating pupae. In 1990, larval mortality in the first instar was 80% (range 9–97% for the individual cohorts). Most larvae died within the fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 8 publications
1
22
0
1
Order By: Relevance
“…• N (Johansen, 1997). The Bertha armyworm, also referred to as the 'Miller Moth' or 'climbing cutworm', is native to North America and is a pest of oilseed and canola production in the northern Great Plains (Ulmer, 2002;Knodel and Ganehiarachchi, 2008).…”
Section: The Cabbage Moth (Mamestra Brassicae) and Bertha Armyworm (Mmentioning
confidence: 99%
See 1 more Smart Citation
“…• N (Johansen, 1997). The Bertha armyworm, also referred to as the 'Miller Moth' or 'climbing cutworm', is native to North America and is a pest of oilseed and canola production in the northern Great Plains (Ulmer, 2002;Knodel and Ganehiarachchi, 2008).…”
Section: The Cabbage Moth (Mamestra Brassicae) and Bertha Armyworm (Mmentioning
confidence: 99%
“…The mortality of eggs, larvae, pupae and larval dispersal of the cabbage moth on white cabbage (B. oleracea var. capitata) was investigated in a series of small-scale field experiments and in the laboratory (Johansen, 1997). The highest mortality was found in young larvae and in hibernating pupae.…”
Section: The Cabbage Moth (Mamestra Brassicae)mentioning
confidence: 99%
“…The cabbage moth Mamestra brassicae (Linnaeus, 1758) (Le pi doptera: Noctuidae) is widely distributed throughout Asia and Europe (Johansen, 1997) and one of the major pests of cabbage in Europe (Finch & Thompson, 1992). Its polyphagous larvae feed mainly on cabbage (Brassica oleracea L., Brassicaceae) and other plants in the genus Brassica, but also on tomato, beet, on ion and some flowers and forest trees (Hill, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Its polyphagous larvae feed mainly on cabbage (Brassica oleracea L., Brassicaceae) and other plants in the genus Brassica, but also on tomato, beet, on ion and some flowers and forest trees (Hill, 1987). The larvae of M. brassicae are attacked by braconid wasps (Johansen, 1997), among which the solitary larval parasitoid, Microplitis mediator (Haliday, 1834) (Hymenoptera: Braconidae), is the most impor tant (Bianchi et al, 2005;Lauro et al, 2005). It is a generalist endoparasitoid that is reported from approximately 40 different noctuid hosts (Mir Khan, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Some authors claim that this pest can have up to three generations per year (Oku, Kobayashi 1974). In northern Europe, it was reported that the cabbage armyworm is a univoltine species (Johansen 1997;Metspalu et al 2004). In central Europe, the bright-line brown-eyes moth also has two generations (Čamprag, Jovanić 2005).…”
mentioning
confidence: 99%